1978
DOI: 10.1128/iai.19.1.146-151.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L1210 leukemia on the susceptibility of mice to Candida albicans infections

Abstract: This study was carried out to determine whether animals bearing L1210 leukemia were more susceptible to candida infection in the absence of immunosuppression and to determine also if the L1210 cells suppressed the inflammatory response of the animal host. Systemic infection was studied by intravenous injection of Candida albicans and checking for the number of candida organisms cultured from the blood and the kidneys. Localized infection was studied by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, it has been indicated that normal defense mechanisms, i.e., complement and other serum factors, macrophages and PMNs, are primarily responsible for host defense against C. albicans infection (7). Johnson et al (5) reported that mice bearing ascites L1210 leukemia exhibited increased susceptibility to systemic Candida infection and also showed a reduction in the accumulation of PMNs. Little was known, however, about augmentation of (6) and in ascites form, exhibited resistance against C. albicans infection.…”
mentioning
confidence: 99%
“…However, it has been indicated that normal defense mechanisms, i.e., complement and other serum factors, macrophages and PMNs, are primarily responsible for host defense against C. albicans infection (7). Johnson et al (5) reported that mice bearing ascites L1210 leukemia exhibited increased susceptibility to systemic Candida infection and also showed a reduction in the accumulation of PMNs. Little was known, however, about augmentation of (6) and in ascites form, exhibited resistance against C. albicans infection.…”
mentioning
confidence: 99%
“…Though the importance of medical treatments is now pointed out for this type of infection, it is thought that the experiments using simple models such as tumor‐bearing mice are needed to solve these problems. There are many papers concerning the increased susceptibility of tumor‐bearing hosts to systemic fungal infections [1–4]. However, the protective activity of tumor‐bearing mice against the most important pathogenic yeast, Candida albicans , infection has been reported in our previous papers [5–7] and by others [8].…”
Section: Introductionmentioning
confidence: 91%